PENGARUH FAKTOR PERSONAL PELAKU USAHA, KEMAMPUAN PENYULUH, DAN PROSES PEMBELAJARAN DALAM PENYULUHAN TERHADAP KOMPETENSI KEWIRAUSAHAAN INDUSTRI KECIL MENENGAH KABUPATEN MAGELANG - Kusumawati, Kiki; Joyoatmojo, Soetarno; M.Bus, Susilaningsih (Jurnal Pendidikan Insan Mandiri, 2015)
The purposes of this study are to determine : 1) the influence of entrepreneurs personal factor to learning process in counseling, 2) the influence of extension officers capability to learning process in counseling, 3) the influence of learning process in counseling to the entrepreneurship competence, 4) the influence of entrepreneurs personal factor to entrepreneurship competence and 5) the influence of the extension officers capability to entrepreneurship competence. This is descriptive quantitative study. The population of the sample was all small-scale entrepreneurs at Kab. Magelang who got counseling from the Cooperatives and Small and Medium Enterprises Department fiscal year 2013. 92 participants were randomly chosen. The instruments used in collecting data are questionnaire, interview and documentation. The data analysis was done through path analysis.The result of this study shows that 1) 19.1% entrepreneurs personal factor influenced the learning process of counseling directly, 2) 26.8% extension officers competence affected the learning process in counseling directly, 3) 5.88% learning process in counseling influenced the entrepreneurship competence directly, 4) 1.92% entrepreneurs personal factor affected the entrepreneurship competence indirectly, 5) 5.29% extension officers competence directly influenced the entrepreneurship competence.Keywords: entrepreneurs personal factor, extension officers capability, learning process in counseling, entrepreneurship competence, small-scale industry